(untitled) (Third Sector Social Economic Review, 2017)
Often in business activities; The concept of innovation, which is defined as therealization of a product (goodsor service), or a process, a new marketing method or a new organizational method, that is improved in new or significantly improved in-house practices, work place organization or external relations, is in close contact with the concept of entrepreneurship have been studied together in studies. Theconcept of entrepreneurship is defined as a learning process that can be evaluated and applied both from the point of view of the individual and the enterprise and from the point of view of the public service institutions. Given the fact that not all businesses have made a special investment in this learning process, ""entrepreneurship management"" is closelytied to the individual performance of enterprise employees and the individual performance following the innovation, especially for small and medium sized enterprises. Inaddition, the social economic networks that are related to each other, that is, businesses that have similar activities in a specific are a sector, are a very important field for following innovative and entrepreneurial activities. Within the scope of this study, it will be investigated whether the organizations that are operating in cooperatives in our country are in innovative activities and whether the give a shape to the relations of innovative processes in are as where they operate jointly. In the research to be conducted by the qualitative research method, the data will be gathered by the interview method and content analysis will be made to some findings about the effect of these activities of the cooperatives in the innovative activities on the entrepreneurship structure.